A Utopia dos Pobres nas Narrativas de Migração no Ceará, Nordeste do Brasil - Rios, Kênia Sousa (Trabalhos de Antropologia e Etnologia, 2020)
The drought is constituted as a narrative mark on the life and the various displacements of the poor of Northeast Brazil. Therefore, the article tries to understand the place of construction of a materialized utopia in the travel and in the act of telling it from an unmistakable familiarity with popular tales in which the ideal place is experienced as mystery, as secret, as fantastic. Crossing the supports of orality, the text presents a possible reading about the displacement and the desire of the poor.